(untitled) (Research, Society and Development, 2022)
The study aimed to assess the cardiovascular, ophthalmic, and electrolytic parameters of pregnant bitches. Ten American Bully bitches, with an average age of 22 ± 3.4 months, were included in this study. The evaluated parameters including the systolic blood pressure, electrocardiogram, Schirmer test 1, corneal sensitivity, intraocular pressure, serum potassium, sodium, ionized calcium, Ca2+, and phosphorus. The evaluations were conducted 3 days after the artificial insemination (day 0: D0) and during the gestational period (D30, D40, and D60). Despite the systolic blood pressure increased (P < 0.01), values were within the normal range in D40 to D60. The electrocardiogram indicated an increase in heart rate at D60 (P < 0.001; within normal values); and elevation of the P-wave and QRS complex durations in all evaluation periods, in comparison to the expected values for the species. Regarding electrolyte analysis, lower Na+ was identified at D30 (P < 0.009) and D40 (P < 0.01). At the same time, the ophthalmic evaluation showed that tear production decreased in D60 compared to the other periods (P < 0.01) but remained within the normal range for the species. In addition, important electrolyte and electrocardiographic correlations were observed at D30 and D60. Our study demonstrated that, despite changes in electrocardiographic, blood pressure, electrolytic, and ophthalmic evaluation, they did not have any impact on physiological state, indicating only an adaptive condition to gestation. However, it is noteworthy that even with such results, the possibility of changes during this period is not ruled out, justifying the need for monitoring pregnant bitches throughout the whole gestational period.